Depocentros Cenozoicos de los Andes Australes durante la apertura del Pasaje de Drake - Ghiglione, Matias; Gallardo Jara, Rocío; Calderón, Mauricio; Fosdick, Julie; Albano, Juan Manuel Ricardo; Kress, Pedro; Raggio, Fernanda
Cretaceous-Cenozoic interaction between the South America and Antarctica plates has been a major driver of kinematics in the Southernmost Andes, imprinting extensional and strike- slip deformation within the foreland in Tierra del Fuego. Late Cretaceous basin inversion and transpression along the Beagle channel was due to their left-lateral relative displacement. Orogen building continued during the Paleogene, together with progression of sedimentation in the associated Austral-Malvinas marine foreland basin system and depocenters migrations. The Eocene early opening of the Drake passage due to Antarctica separation, involved the combination of strike-slip and extensional tectonics, superposed to the previously consolidated orogen. A series of latest Paleocene–early Eocene fault-related extensional depocenters can be recognized in the Austral and Malvinas basins, which represent a direct indication of continental lithospheric stretching preceding the opening of embryonic basins in the West Scotia Sea. A middle-late Eocene compressional stage followed, characterized by rapid migration of the orogenic front and establishment of a widespread wedge-top depocenter. Since the Oligocene inception of oceanic spreading in the West Scotia Sea, strike-slip deformation has dominated, concentrated along the North Scotia ridge-Magallanes-Fagnano fault zone. As a result, late Cenozoic continental pull-apart basins are registered in a hinterland position. Coeval retroarc Miocene sedimentation includes an important continental volcaniclastic component and distributary system funneling sediments to deep marine basins. In this context, tectonic loading, dynamic subsidence, and transtension/pull-apart extension seems to be superposed; alternatively, they may be partitioned processes and geographically distributed. We present a synthesis of this history of changing tectonic regimes and depocenters migration in the southernmost Andes and the Austral basin from and discuss the implication of new detrital zircons provenance data. ...